DERMATOGLYPHIC MARKERS AND THE MUSCULAR FORCE OF STUDENTS FROM 7 TO 17 YEARS. (Fiep Bulletin - online, 2014)
This study aimed at analyzing the dermatoglyphic features in the different levels of muscular force of 197 male students, with age group from 7 to 17 years, distributed into four groups, according to the force levels: G I - Weak (n=16); G II - Regular (n=99); G III - Good (n=71) and G IV - Excellent (n=10). In order to accomplish the goal, the fingerprints were collected through the Dermatoglyphic protocol and the 1RM test for the identification of the force. The results indicated that the average values of the D10 digital formulas and the addition of the total amount of lines of the SQTL fingers did not present significant differences. However, the averages of the sum of the amount of lines of the first and fifth finger of the right hand were different statistically, being thus RHSTAL 1 (F = 3,732; p = 0,012) and RHSTAL 5 (F = 2,780; p = 0,042). It was Observed that the strongest individuals G IV, presented the potentialization of the phenotype, muscular strength, through the pure speed as demonstrated in the genotype, due to the superior indexes of " L " being larger than W. The amount of lines in each finger of the hands was similarly mirrored with D10 and low STAL. The same occurred in G I, with the values D10 and STAL, relatively high. It was concluded that the likeness found in the dermatoglyphic features occurred due to the natural selection of the groups, which were influenced by the variations of the levels of force.
Keywords: Genetic markers; fingerprints; 1RM